2023
DOI: 10.1037/ort0000683
|View full text |Cite
|
Sign up to set email alerts
|

Knowing Who You Are (Becoming): Effects of a university-based elder-led cultural identity program on Alaska Native students’ identity development, cultural strengths, sense of community, and behavioral health.

Abstract: In part due to cultural loss and identity disruption over many generations from colonial and neocolonial forces, significant emotional/behavioral health disparities exist among Alaska Native (AN) people. Such forces are apparent in higher education, where many AN students feel othered and are more likely to withdraw without a degree than their nonnative counterparts. A strong cultural identity has been found to buffer psychosocial difficulties. The AN Cultural Identity Project (CIP) was developed from the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…CIP was developed in this vein, with its intention to support AN students' cultural identity development to promote their well‐being and help them to persist at the university. While quantitative data revealed that CIP had numerous positive effects on indicators of these individual outcomes (see Buckingham et al, in press), focus group findings pointed to the many processes of CIP as a counterspace that positively impacted everyone in the space—students, Elders, and other program personnel alike—shaped the space itself, and had ripple effects beyond the space.…”
Section: Discussionmentioning
confidence: 99%
“…CIP was developed in this vein, with its intention to support AN students' cultural identity development to promote their well‐being and help them to persist at the university. While quantitative data revealed that CIP had numerous positive effects on indicators of these individual outcomes (see Buckingham et al, in press), focus group findings pointed to the many processes of CIP as a counterspace that positively impacted everyone in the space—students, Elders, and other program personnel alike—shaped the space itself, and had ripple effects beyond the space.…”
Section: Discussionmentioning
confidence: 99%